Regulation, credit risk transfer, and bank lending - Thilo Pausch; Peter Welzel (Universität Augsburg, Institut für Volkswirtschaftslehre, 2011)
We integrate Basel II (and III) regulations into the industrial organization approach to banking and analyze lending behavior and risk sensitivity of a risk-neutral bank. The bank is exposed to credit risk and may use credit default swaps (CDS) for hedging purposes. Regulation is found to induce the risk-neutral bank to behave in a more risk-sensitive way: Compared to a situation without regulation the optimal volume of loans decreases more as the riskiness of loans increases. CDS trading is found to interact with the former effect when regulation accepts CDS as an instrument to mitigate credit risk. Under the Substitution Approach in Basel II (and III) a risk-neutral bank will over-, fully or under-hedge its total exposure to credit risk conditional on the CDS price being downward biased, unbiased or upward biased. This interaction promotes the intention of the Basel II (and III) regulations to 'strengthen the soundness and stability of banks', since capital adequacy regulation without accounting for the risk-mitigating effect of CDS trading would stimulate a risk-neutral bank to take more extreme positions in the CDS market.
urn:nbn:de:bvb:384-opus4-711055
Keywords: G21; G28; 330; Bank; Credit business; Credit risk; Basel Accord; Credit Default Swap; Bank; Kreditgeschäft; Kreditrisiko; Basler Akkord; Credit Default Swap; Theorie